An Anatomical Study of Pittadhara Kala w.s.r Duodenal Ulcer - A Review. - Kumari, Nitu; Mishra, Vikas; Priyanka (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda has played important key role in Alternative Medicine, Traditional Ayurveda science. In Ayurveda basic principles like Tridosha, Panchmahabhuta, Dravyaguna are explained briefly. Acharya sushruta has explained Kala Sharir in 4th Chapter of Sharirasthana Gharbhashariramadhyaya. Total seven kala are present in the Human body and these are the limiting membranes between Dhatu and Aashaya. Pittdhara Kala is sixth in order, situated in between Pakwashaya and Amashya (i.e. Pakwaamashya). Pittdharakala can be correlated with mucous membrane of small intestine. Upper part of small intestine is known as duodenum. Duodenal ulcer is one of the peptic ulcers. Duodenum ulcer are formed due to damage of barrier, which is made up by cells of duodenum from mucus membrane. The main cause of mucus membrane is infection with bacteria called Helicobacter Pylori or H. Pylori. The bacteria cause the lining of your duodenum to become inflamed and an ulcer can form. Present paper is about to explore involvement of Pittadhara Kala in duodenal ulcer